ASSESSMENT OF THE IMPACT OF HORMONE THERAPY ON THE QUALITY OF LIVE OF WOMEN WITH BREAST CANCER (CIPEEX, 2025)
Introduction: Breast cancer is the most prevalent malignant tumor and the most frequently diagnosed among women. It presents different biological subtypes, among which the hormone receptor-positive is particularly relevant. The standard adjuvant treatment to reduce the risk of recurrence and mortality for this subtype is endocrine therapy. This therapy has proven efficacy and is recommended for continuous use for a minimum of five years. However, given its importance, it is necessary to assess the well-being of the patients who use it. Objective: To evaluate the impact of hormone therapy on the quality of life of women with breast cancer. Methods: This is an integrative literature review based on scientific studies in the English language from the Virtual Health Library (VHL) and PubMed virtual databases, published within the last 5 years (2020-2025). Eleven primary studies, quantitative or qualitative, were selected, which directly addressed the impacts on the quality of life during endocrine therapy in women with breast cancer. Scientific articles that were literature reviews, meta-analyses, duplicate articles, or that did not address these impacts were excluded. The Health Sciences Descriptors (DeCS) used were: “Antineoplastic Agents, Hormonal”, “Breast Neoplasms” and “Quality of Life”. Results: This review observed that hormone therapy significantly impacts the quality of life of the women who use it, leading to a reduction in their well-being. This impact is mainly related to the side effects associated with the therapy, which, despite being low-grade, can deteriorate quality of life by persisting over time. Among the adverse events reported in the included studies, one article identified vasomotor symptoms, urinary symptoms, headaches, ocular toxicity, metabolic disorders such as weight gain, concerns regarding fertility, and nausea and vomiting. Insomnia and bone loss were reported in two studies; mood swings and cognitive difficulties, especially those related to memory and language, in three; and fatigue, sexual dysfunction, and gynecological symptoms in four. However, the most frequently reported adverse effects were hot flashes, psychological disorders, and musculoskeletal symptoms, which were observed in seven, six, and five studies, respectively. Conclusions: Therefore, although hormone therapy confers beneficial effects on breast cancer control, this review demonstrates that the therapy unfavorably impacts the quality of life of women undergoing treatment, affecting the physical, psychological/emotional, social, and functional domains. In this context, considering that this treatment is essential for a good prognosis, it becomes imperative to implement strategies to promote and support patients. These strategies should aim to precociously identify the different symptoms that may arise, to mitigate suffering during treatment, and to prevent low adherence to or discontinuation of endocrine therapy.
Keywords: antineoplastic agents; hormonal; breast neoplasms; quality of life